COMPARISON OF ACTUAL COSTS AND INA-CBGS TARIFFS UNDER THE JKN SYSTEM: FACTORS INFLUENCING HOSPITAL TARIFFS - Yusran, Yusran; Ningrum, Vitarani Dwi Ananda; Sari, Seftika (Jurnal Farmasi Sains dan Praktis, 2025)
The Social Security Administration (BPJS), as the organizer of the National Health Insurance (JKN) program, applies the INA-CBGs tariff system. In the INA-CBGs system, payments are based on grouping patient cases into specific categories according to diagnoses and medical procedures performed. The hospital payment system has shifted from a fee-for-service model to a prospective payment system. BPJS no longer considers the actual costs incurred by hospitals but instead focuses on the standardized INA-CBGs tariffs. This study aims to examine previous research comparing real hospital costs with INA-CBGs tariffs, and to identify the factors that contribute to discrepancies between the two. A narrative literature review was conducted by searching for articles in the PubMed and Google Scholar databases. Data extraction was performed using predefined inclusion and exclusion criteria, and the article selection process followed the PRISMA method. From the selected articles, seven studies related to the comparison of real hospital costs and INA-CBGs tariffs and the factors influencing these discrepancies were identified. The review found that factors influencing real costs include the length of hospital stay, treatment class level, patient severity, and the presence of comorbidities.